Gallery Sdn. Bhd. / Asrul Nizam Saharuddin... [et al.] - Saharuddin, Asrul Nizam; Zainal, Muhamad Ezham; Abdul Manap, Fakhirudin; Ibrahim, Faisal (2001)
Our company name is Gallery Sdn. Bhd. the concept of our business is educational. We choose educational because it has potential development, especially the increase number of higher educational institution.